2021
DOI: 10.1093/rheumatology/keab506
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of shoulder and knee improves the accuracy of the 2012 EULAR/ACR provisional classification criteria for polymyalgia rheumatica

Abstract: Objective Recent studies suggest that the knee is frequently involved in polymyalgia rheumatica (PMR). In this study, we aimed to determine whether the ultrasound assessment of the shoulder and knee discriminates between PMR and other differential diagnoses and improves the accuracy of the 2012 EULAR/ACR provisional classification criteria for PMR. Methods We consecutively enrolled 81 untreated patients who received a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The precocious use of US in patients with PMR has already demonstrated an increase of diagnostic specificity [ 3 , 21 , 42 44 ]. Our results show that the overall management of the disease does not change with the introduction of US at onset, as we could not demonstrate significant differences in the incidence of disease flares and prescription of DMARDs among the various management modalities (with or without US).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precocious use of US in patients with PMR has already demonstrated an increase of diagnostic specificity [ 3 , 21 , 42 44 ]. Our results show that the overall management of the disease does not change with the introduction of US at onset, as we could not demonstrate significant differences in the incidence of disease flares and prescription of DMARDs among the various management modalities (with or without US).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in terms of follow-up and long-term outcome, US displays interesting insights, although only a few papers had previously investigated the role of imaging procedures in PMR, displaying conflicting evidence. Some studies [ 45 ] evidenced a correlation between shoulder PD and a number of relapses, while others focused on soft tissue hypervascularization [ 43 ] or extrasynovial involvement [ 42 ] to increase the diagnostic specificity of ACR/EULAR criteria [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, US of the hip can be time-consuming, and uncomfortable for the patient, and therefore, it is not always feasible in clinical practice, somewhat limiting the real-world application of the 2012 EULAR/ACR provisional classification criteria. With advancements in imaging modalities, we are coming to appreciate the involvement of anatomical areas outside of the hips and shoulders in PMR, most notably the knees and interspinous processes [27,28,81,82] . Accordingly, one group assessed the role of US of the shoulder and knee in discriminating newly diagnosed PMR from other differential diagnoses, and found that US assessment of the tendon and ligament-related lesions in both shoulders (long head of biceps, supraspinatus or subscapularis tendon) and both knees (popliteus tendon or medial or lateral collateral ligament) increased the diagnostic accuracy of the 2012 EULAR/ ACR provisional classification criteria for PMR [83] .…”
Section: Imagingmentioning
confidence: 99%
“…An additional retrospective study by the same group including 120 patients with pelvic girdle pain of unknown origin further confirmed this unique pattern of inflammation in the specific pelvic tendinous and capsular structures in those with PMR [88] . Moreover, MRI has enabled the novel identification of the involvement of interspinous bursa in PMR [81,82] .…”
Section: Imagingmentioning
confidence: 99%
“…[ 26 ] A recent study also showed that tenosynovitis, tendinitis, and ligament inflammation in the shoulder and knee detected by MSUS assessment may improve the accuracy of the 2012 EULAR/ACR provisional classification criteria for PMR. [ 48 ]…”
Section: Introductionmentioning
confidence: 99%